HOW MULTIPLE BRANCHES OF MATHEMATICS UNITE THE MOBIUS STRIP WITH MULTIPLE PHENOMENA IN PHYSICS AND COSMOLOGY - Bartlett, Rodney (IJRDO -JOURNAL OF MATHEMATICS, 2023)
Question – How does the Riemann Hypothesis Support Topological Propulsion and Faster-than-light Travel? Answer – a) Using the axiom that there indeed are infinitely many nontrivial zeros on the critical line (calculations have confirmed the hypothesis to be true to over 13 trillion places), the critical line is identified as the y-axis of Wick rotation. This suggests the y-axis is literally infinite and that infinity equals zero. In this case, it is zero distance in time and space. Travelling zero distance is done instantly and is therefore faster-than-light travel. b) Wick rotation is essential to this article’s description of a topological (mathematical) universe and the Riemann hypothesis’ identification with Wick means the hypothesis doesn’t just apply to the distribution of prime numbers but also applies to the fundamental structure of the mathematical universe’s space-time. An absolutely essential ingredient of time travel by applied maths is being able to journey into the remote past and future. For this reason, a paragraph about the coexistence of past, present, and future (without such coexistence, time travel could never be a possibility) is included in a section titled “Riemann Hypothesis and Wick Rotation Support Time Travel into the Past and Future”. This article provides insights into travelling at significant fractions of – as well as faster than - light, the Higgs boson and field, electroweak interaction, dark matter, dark energy, other dimensions, space-time (eg the expanding-universe question and time travel), quantum mechanics, quantum computers, the Riemann hypothesis, and Unidentified Flying Objects.  The article is also a brief summary discussing how the Matrix, the Riemann hypothesis, quaternions, Wick rotation, and imaginary numbers unite topology’s Mobius strip with known and unknown dimensions as well as the Higgs boson, Higgs field, dark matter, dark energy, antigravitons, and the static universe. The article also explains Unidentified Flying Objects as the result of future human technology.